Combating Spurious Correlations in Loose‐fitting Garment Animation Through Joint‐Specific Feature Learning - Diao, Junqi; Xiao, Jun; He, Yihong; Jiang, Haiyong (Computer graphics forum, 2023)
We address the 3D animation of loose‐fitting garments from a sequence of body motions. State‐of‐the‐art approaches treat all body joints as a whole to encode motion features, which usually gives rise to learned spurious correlations between garment vertices and irrelevant joints as shown in Fig. 1. To cope with the issue, we encode temporal motion features in a joint‐wise manner and learn an association matrix to map human joints only to most related garment regions by encouraging its sparsity. In this way, spurious correlations are mitigated and better performance is achieved. Furthermore, we devise the joint‐specific pose space deformation (PSD) to decompose the high‐dimensional displacements as the combination of dynamic details caused by individual joint poses. Extensive experiments show that our method outperforms previous works in most indicators. Moreover, garment animations are not interfered with by artifacts caused by spurious correlations, which further validates the effectiveness of our approach. The code is available at https://github.com/qiji77/JointNet.